Brain Amide Proton Transfer Imaging of Rat With Alzheimer’s Disease Using Saturation With Frequency Alternating RF Irradiation Method - Wang, Runrun; Chen, Peidong; Shen, Zhiwei; Lin, Guisen; Xiao, Gang; Dai, Zhuozhi; Zhang, Bingna; Chen, Yuanfeng; Lai, Lihua; Zong, Xiaodan; Li, Yan; Tang, Yanyan; et al. (Frontiers in Aging Neuroscience, 2019)
Amyloid-β (Aβ) deposits and some proteins play essential roles in the pathogenesis of Alzheimer’s disease (AD). Amide proton transfer (APT) imaging, as an imaging modality to detect tissue protein, has shown promising features for the diagnosis of AD disease. In this study, we chose 10 AD model rats as the experimental group and 10 sham-operated rats as the control group. All the rats underwent a Y-maze test before APT image acquisition, using saturation with frequency alternating RF irradiation (APTSAFARI) method on a 7.0 T animal MRI scanner. Compared with the control group, APT (3.5 ppm) values of brain were significantly reduced in AD models (p < 0.002). The APTSAFARI imaging is more significant than APT imaging (p < 0.0001). AD model mice showed spatial learning and memory loss in the Y-maze experiment. In addition, there was significant neuronal loss in the hippocampal CA1 region and cortex compared with sham-operated rats. In conclusion, we demonstrated that APT imaging could potentially provide molecular biomarkers for the non-invasive diagnosis of AD. APTSAFARI MRI could be used as an effective tool to improve the accuracy of diagnosis of AD compared with conventional APT imaging.